1984
DOI: 10.1002/j.2330-8516.1984.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Integration of Severely Handicapped Students in Regular Education and Community Settings

Abstract: The Education for All Handicapped Children Act (P. L. 94–142) requires that all children have access to free appropriate public education in the least restrictive environment. As this law is applied to severely handicapped (SH) students, the requirements of an appropriate education may compete with the requirements of education in the least restrictive environment. The question addressed by this report is whether integration of SH students into regular schools can constitute a “least restrictive setting” witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…In addition, the organization's most prominent evaluator, Samuel Ball, departed to take an academic appointment in his native Australia. The work that remained investigated the effects of instructional software like the IBM Writing to Read program (Murphy and Appel 1984), educational television (Murphy 1988), alternative higher education programs (Centra and Barrows 1982), professional training (Campbell et al 1982), and the educational integration of students with severe disabilities (Brinker and Thorpe 1984). Whereas funding for evaluation was in decline, support for policy analysis grew.…”
Section: Educational Evaluation and Policy Analysismentioning
confidence: 99%
“…In addition, the organization's most prominent evaluator, Samuel Ball, departed to take an academic appointment in his native Australia. The work that remained investigated the effects of instructional software like the IBM Writing to Read program (Murphy and Appel 1984), educational television (Murphy 1988), alternative higher education programs (Centra and Barrows 1982), professional training (Campbell et al 1982), and the educational integration of students with severe disabilities (Brinker and Thorpe 1984). Whereas funding for evaluation was in decline, support for policy analysis grew.…”
Section: Educational Evaluation and Policy Analysismentioning
confidence: 99%
“…Integrated services are described throughout the literature as &dquo;best practice&dquo; based on social-ethical, legal-legislative, and psychological-educational arguments (e.g., Bricker, 1978;CEC 1979;Fox et al, 1986;Guralnick, 1976Guralnick, , 1981TASH, 1979;Wilcox & Bellamy, 1982). Research studies over the past 10 years have demonstrated the educational and social benefits of integration for both preschool and school-age students with severe handicaps (e.g., Beckman & Kohl, 1987;Brinker & Thorpe, 1984;Fink, 1979;Guralnick, 1981;Jenkins, Speltz & Odom, 1985;Strain, Hoyson, & Jamieson, 1985). However, integrated services are not standard practice (Rostetter, Kowalski & Hunter, 1984), primarily because of funding patterns that have discouraged the development of integrated early childhood services (Gentry & Olson, 1985).…”
mentioning
confidence: 96%
“…Teacher characteristics also are associated with educational placement. In particular, studies suggest that years of teaching experience, participation in in-service training on integration (Brinker & Thorpe, 1984, and teacher advocacy for integration (Filler et al, 1986;Hamre-Nietupski et aI., 1988) are related to the delivery of educational services in integrated environments.…”
mentioning
confidence: 97%